2002
DOI: 10.1248/bpb.25.597
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Putative Hydroxylated Thalidomide Metabolites on Blood Vessel Density in the Chorioallantoic Membrane (CAM) Assay and on Tumor and Endothelial Cell Proliferation.

Abstract: Angiogenesis, the process of blood vessel formation from pre-formed vessels, has recently become a primary target of anticancer therapy. This is due in part to the finding that removing the blood supply to a tumor can not only prevent further growth but can also starve the existing cells to death.2) In the past several years there have been many potential anti-angiogenic agents developed acting by many mechanisms including interruption of growth factor receptor phosphorylation, [3][4][5] growth factor-receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
31
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 60 publications
3
31
0
Order By: Relevance
“…Despite several studies displaying the need of metabolic activation of racemic Thd, we demonstrated an inhibition of gene transcription with hydrolysis products only (Kenneth et al, 1998). Similar reports regarding the effects of hydroxylation without bioactivation have been published previously (Marks et al, 2002).…”
Section: Thalidomide Inhibits Gc-rich Promoter Gene Transcription 419supporting
confidence: 86%
“…Despite several studies displaying the need of metabolic activation of racemic Thd, we demonstrated an inhibition of gene transcription with hydrolysis products only (Kenneth et al, 1998). Similar reports regarding the effects of hydroxylation without bioactivation have been published previously (Marks et al, 2002).…”
Section: Thalidomide Inhibits Gc-rich Promoter Gene Transcription 419supporting
confidence: 86%
“…Recent research has shown that the drug has antitumoral properties, and promising results from thalidomide treatment in patients with myeloma, myelodysplastic syndrome, and variety of solid tumors has been reported [35] . However, thalidomide has been shown to require bio-activation to exert its anti-angiogenic effect in isolated blood vessels and endothelial cells [36,37] . Moreover, thalidomide displayed varying antiangiogenic activities in endothelial cells (ECs) in the literature [38,39] .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we reported the antiangiogenic activities of several putative metabolites of thalidomide (26). Our ongoing search for potent antiangiogenic thalidomide analogues revealed a compound, 5-hydroxy-(2,6-diisopropylphenyl)-1H-isoindole-1,3-dione (5HPP-33; Fig.…”
Section: Introductionmentioning
confidence: 99%